Experimental Study on the Influence of Bevel Geometry in SMAW Welding on Tensile Strength - A. Khalid; A. Barry; Y. R. Fauzi (Asian Journal of Mechanical Engineering, 2025)
The strength of welded joints is influenced by various factors, one of which is the structural transformation caused by the heat generated during the welding process. To ensure a high-quality connection between two metal components, proper welding techniques and appropriate joint design—particularly the bevel geometry—are essential. In Shielded Metal Arc Welding (SMAW), critical parameters include current, voltage, polarity, and joint angle, all of which contribute to weld quality. This study investigates the effect of different bevel types on the tensile strength of welded joints in medium carbon steel. Welding was performed using RB-26 electrodes at a current of 100 A in the 1G position, with three bevel variations: V, I, and double V. One specimen was prepared for each bevel type. The results indicate that bevel geometry significantly affects the mechanical performance of the weld. Among the tested variations, the V bevel produced the highest tensile strength, outperforming the I and double V bevels. This result is attributed to the lower distortion angle observed in the V bevel configuration. Overall, achieving optimal weld quality is closely related to both joint design and welding technique.